Ardl Panel's Capability In Maintaining Economic Stability During Covid-19 Asean Founder Countries - Ade Novalina (International Journal of Science, Technology & Management, 2021)
The slowdown in the world economy due to the COVID-19 pandemic has become one of the triggers for increased analysis in the economic sector to find the proper steps to protect the economy from the shadow of the crisis. However, most research is still focused on several separate policies, which makes the analysis results still seem bleak. This research was conducted using the ARDL panel approach to analyze the ability of endurance policy to maintain a balance between aggregate demand and supply in ASEFO countries. The data used is secondary data (time series) from 2009 – 2019. The analysis results show that the leading indicators of controlling GDP in ASEFO countries on a panel basis are INF, NPL, GOV, LDR. Meanwhile, the leading indicators of the effectiveness of the variables are INF and GOV. Thus, government spending during the pandemic must still be controlled not to cause inflation which is a threat to the economy.